Clinical Characteristics of Patients with Type 2 Diabetes Mellitus Receiving a Primary Total Knee or Hip Arthroplasty - Annalisa Na; Laurie Jansky; Zbigniew Gugala (Journal of Diabetes Research)
Aim. The purpose of this study is to explore clinical characteristics of patients with T2DM receiving a primary knee (TKA) or hip (THA) arthroplasty to patients without T2DM receiving a TKA or THA and patients with T2DM with no history of osteoarthritis (OA). Methods. The study included a retrospective database review of 500 consecutive primary TKA or THA identified with ICD-9 codes and 100 consecutive T2DM patients. Patients who received a TKA or THA were screened for inclusion and exclusion and divided into with or without T2DM groups. A comparison group of patients with T2DM only without arthroplasty was screened to exclude patients with a history of OA or arthroplasty. All groups were compared based on demographic and relevant comorbidity differences. OA characteristics, including OA and previous arthroplasty of the involved and contralateral joints, were compared between patients with and without T2DM receiving a TKA or THA. Finally, patients with T2DM with and without TKA or THA were compared for T2DM differences. Results. Study results found that among those receiving a primary arthroplasty, patients with T2DM were more likely to be obese and older and reported cardiovascular, urinary, dyslipidemia, and peripheral neuropathy than those with T2DM. Among the T2DM individuals, those receiving an arthroplasty surgery were older and obese and more likely to report peripheral neuropathy; however, those with T2DM with no OA were more likely to report atherosclerosis and cardiovascular disease. Within the arthroplasty subgroup of individuals with T2DM, those requiring antidiabetic medication were 4.5 times more likely to have contralateral OA or arthroplasty. Conclusions. The results of this study suggest that patients with T2DM requiring a primary arthroplasty are a unique subgroup that requires careful considerations as they are often older, have obesity, and specific comorbidities predisposing to worse postoperative outcomes than their non-T2DM arthroplasty counterparts. Therefore, clinical practice and future studies must consider strategies that would limit OA and arthroplasty management delays while accounting for comorbidities and patient characteristics.